1990
DOI: 10.1002/jcp.1041450106
|View full text |Cite
|
Sign up to set email alerts
|

Bumetanide‐sensitive Na+ /K+ /Cl− transporter is stimulated by phorbol ester and different mitogens in quiescent human skin fibroblasts

Abstract: In this study we investigated the correlation between the mitogenic effect and stimulation of Rb+ (K+) fluxes in human skin fibroblasts treated by purified growth factors. Both K+ transporters, bumetanide-sensitive and ouabain-sensitive, are stimulated 2-3-fold after addition of either fetal calf serum or purified recombinant growth factors to quiescent G0/G1 human skin fibroblasts. Three groups of mitogens were compared: i) the phorbol ester 2-O-tetradecanoyl-phorbol-13-acetate (TPA); ii) growth factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…Serum regulates membrane channels (25) and transporters (26). In the present study, we found that serum factors were important to maintain the basal activity of K-Cl COT in VSMCs because serum deprivation for 24 h abolished this activity (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Serum regulates membrane channels (25) and transporters (26). In the present study, we found that serum factors were important to maintain the basal activity of K-Cl COT in VSMCs because serum deprivation for 24 h abolished this activity (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Serum plays multiple roles in the regulation of the activity of ion channels and transporters in cultured cells (26,29). To examine whether serum has an effect on basal K-Cl COT activity in primary cultures of rat VSMCs, cells were serum deprived for 24 h and K-Cl COT activity was subsequently measured.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ration of serum deprivation, and the serum concentration in the arrest medium, were analyzed . We have shown that in cultures of human skin fibroblasts arrested under optimal conditions, the bumetanide-sensitive Na+/K+/Cl-cotransport is stimulated by two-to threefold after the addition of fetal calf serum, or purified recombinant growth factors (Panet and Allan, 1990) . In the present study, we analyzed, with the use of specific inhibitors furosemide and bumetanide, whether stimulation of the Na+/K+/Cl -cotransporter by serum growth factors is essential for human fibroblast proliferation .…”
mentioning
confidence: 99%